Economy, finance and business in southeastern and central Europe : proceedings of the 8th International Conference on the Economies of the Balkan and Eastern European Countries in the Changing World (EBEEC) in Split, Croatia, 2016 /: proceedings of the 8th International Conference on the Economies of the Balkan and Eastern European Countries in the Changing World (EBEEC) in Split, Croatia, 2016. ([2018]) - Unknown
No abstract available